Sie sind auf Seite 1von 15
      1+ √ 2 5 + 1 − √ 2 5 1 1
 

 

 

1+ √ 2 5 + 1 − √ 2 5 1 1 1 1 2
1+ √ 2 5 + 1 − √ 2 5
1
1
1
1
2
1
1
3
3
1
1
4
6
4
1
1
5
10
10
5
1
1+ √ 2 5
=
1+5 √ 2 + 10 √ 2 2 + 10 √ 2 3 +5 √ 2 4 + √ 2 5
1 − √ 2 5
=
1 − 5 √ 2 + 10 √ 2 2 − 10 √ 2 3 +5 √ 2 4 − √ 2 5
1+ √ 2 5
+ 1 − √ 2 5
=
2
+ 20 √ 2 2
+ 10 √ 2 4
=
2 + 20 · 2 + 10 · 4 = 82

8 4 √ 2 3 2 − 3 2 100 log 10 √ 3 10
8 4 √ 2
3
2 − 3
2
100
log 10 √
3
10

8 4 2

3

2 − 3 2
2 − 3
2

= 2 3 3 4 · 2 2 · 2 3 =2 3· 4

1

2

3 +

1

2 + 3

2

=2 6 = 64

log 10 10 = log 10 (100) log 10 10 3 =2 3 log 10 (10) = 6

100

3

1

1

1

3 3 = 5

3

 

 

sin 2 (120 ) + cos(240 ) + tan(315 )

 
 

0

2 π

0 . 5

0

90

cos(1000 )

• sin(120 ) 180 − 120 = 60 sin(120 ) sin(120 ) = √ 3

sin(120 )

180 120 = 60

sin(120 )

sin(120 )

=

3

2

cos(240 )

90

270

 

cos(240 ) =

1

 
 

2

315

45

1

 

sin(315 )

=

1

 

2

 

1

 

cos(315 ) =

 

2

 
   

1

√ 2 1
2
1

2

= 1

 

tan(315 ) =

sin(315 )

 

=

 

cos(315 )

 

sin 2 (120 ) + cos(240 ) + tan(315 )

=

=

sin(x)

=

1

2

3

2

2

1

2 1

3

4

2

4 4

4 = 3

4

2 1 − 2 − 1 3 4 − 2 4 − 4 4 = −

0 . 5

0 2 π

3π

π

= 7π

3 6

2

[0; 2 π ]

x = 7π

6

x = 11π 6

cos(1000 )

0

90

360

cos(1000 ) =

cos(1000 3 · 360 )

= cos(80 )

 

cos(

80 )

=

cos(80 )

 

cos(α) = sin(90 α)

 

cos(1000 ) = cos(80 ) = sin(10 )

 

10

 

A = { 1 , 2 , 3 } B = { x| x(x −
A = { 1 , 2 , 3 } B = { x| x(x − 2)(x − 4)(x − 6) = 0 }
{ 0 , 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 }
A ∪ B
A
0
∈ { 0 }
0 ⊂ { 0 }
{ 0 } ∈ { 0 } { 0 } ⊂ { 0 }
∈ { 0 }
∅ ⊂ { 0 }
∅ ∈ {∅}
∅ ⊂ {∅}
{ 0 , 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9}
A =
{ 1 , 2 , 3 }

B = { 0 , 2 , 4 , 6 }

 

A B

= { 0 , 1 , 2 , 3 , 4 , 6 } = { 5 , 7 , 8 , 9 }

A

∅ { 1 , 2 }

 

{

1 }

{ 2 } { 2 , 3 }

 

{ 3

}

{ 1 , 3 }

{ 1 , 2 , 3 }

 

0 ∈ { 0 } { 0 } ⊂ { 0 } ∅ ⊂ { 0 } ∅ ∈ {∅} ∅ ⊂ {∅}

 

0

⊂ { 0 } 0

{ 0 }

∈ { 0 }

0

{ 0 }

{ 0 }

{ 0 }

 
 

M ∩ N ∪ L
M ∩ N ∪ L

M

L

N

L N

 

M \ (L N )

 

M (L N ) M L N

 

N L

L

N

M M ∩ N ∪ L N ∪ L
M
M ∩ N
∪ L
N ∪ L

1 6 5 (2 a − 3)(a − 1) − 4 a 2 − 9
1
6 5
(2 a − 3)(a − 1) − 4 a 2 − 9 + 4 a 2 +2 a − 6
1
√ 1 − x 2 +
1+ x 2
1
1+
1− x 4
√ ab 3
3
a
− 3 b
1
ln(x 2 − y 2 ) + ln x − y − ln (x + y ) 2

(2)

=

1

6

5

(1)

=

6

(2 a 3)(a 1) (2 a 3)(2 a + 3) + (2 a + 3)(2 a 2)

(4 a 2 + 2 a 6) (12 a 2 24 a + 12) + (10 a 2 25 a + 15)

1

5

(2 a 3)(a 1) 4 a 2 9

4 a 2 +2 a 6

(3)

=

+

(2 a + 3)(2 a 2) 6(a 1)(2 a 2) + 5(2 a 3)(a 1)

(2 a 3)(a 1)(2 a + 3)(2 a 2) 2 a 2 + a 3

=

(4)

=

(2 a 3)(a 1)(2 a + 3)(2 a 2)

(2 a 3)(a 1)(2 a + 3)(2 a 2)

(a 1)(2 a + 3)

(5)

1

=

(2 a 3)(a 1)(2 a + 3)(2 a 2)

(2 a 3)(2 a 2)

 

1+

x 4 = 1 x 4 +1

1

1

1 x 4

1 x 4

1 √ 1 − x 2 + √ 1+ x 2 1 1+
1
√ 1 − x 2 +
1+ x 2
1
1+

1x 4

(3)

=

(1)

=

1 x 2 +

1

1+ x 2 1 x 4

1 x 4 +1

(2)

=

1 x 4 1 x 2 + 1 x 4

1+

x

2

1 x 4 +1

=

1 x 4 1 x 2 + (1+ x 2 )(1x 2 )

1+ x 2

1 x 4 +1

(4)

=

1 x 4 1 x 2 + 1 x 2

1 x 4 +1

(5)

=

1 x 4 +1 1 x 2

1 x 4 +1

(6)

= 1 x 2

 
√ ab 3 a − 3 b = 3

ab 3 a 3 b =

3

3 ab 3 a − 6 b 2 =
3
ab 3
a − 6 b 2 =

a 6 · a · b 3 · b 2

6

=

6

a 7 b

1  x 2 − y 2 1 x − y ln(x 2 − y
1
 x 2 − y 2
1
x − y
ln(x 2 − y 2 ) + ln x − y − ln (x + y ) 2 = ln 
 =
(x + y ) 2
(x − y )(x + y )
(x + y ) 2 (x − y
1
= ln
) = ln (x + y ) = − ln(x +
y )
2
(sin(x) + cos(x)) 2 −
tan(x) + cot(x)
sin(− x) + cos(− x) + sin π
− x + cos π − x
2
2
cos(x + π ) + cos(x + 2 π ) + cos(x + 3 π )

sin 2 (x) + cos 2 (x)=1

sin 2

(x)

=

(sin(x)) 2

2

(sin(x) + cos(x)) 2 tan(x) + cot(x) (1) = sin 2 (x) + cos 2 (x) + 2 sin(x) cos(x)

=1

2

sin( x ) ) + cos( x )

sin( x )

cos( x

=

(2) = 1 + 2 sin(x) cos(x) 2 sin(x) cos(x) (x) (3) = 1 + 2 sin(x) cos(x) 2 sin(x) cos(x)

cos 2 (x) + sin 2

1

(4)

= 1

sin(x) + cos(x) + sin π

x + cos π

x = sin(x) + cos(x) + cos ( x) + sin (x) cos(x) + cos(x) cos(x)

2

2

cos(x + π ) + cos(x + 2 π ) + cos(x + 3 π )

=

=

2 cos(x)

cos(x) = 2

a 2 3 b − 4 5 3 1 2 3 5 a b −
a
2
3 b − 4
5
3
1
2 3
5
a b −
2
2 sin(90 − α) + cos(α + 180 )
tan(α + 90 ) − cot(α − 180 )
4
2 sin 2 (x) − 3 cos 2 (x)+
1 + tan 2 (x)
1
1
ln(x) − 3 ln(y ) + ln(y 3 )+ 3 4 ln(
ln(x + y ) ln(x − y )
x )

a

2 3 b 4

5

3 5 a 2 b − 1
3
5
a
2
b − 1

2 3

=

a 2

3 3

2

· 3

5

b 4

5

(

1

2 ) · 3

5 = a

2027 b 8+3

30

10

= a

7

30 b 1

2

2 sin(90 α) + cos(α + 180 )

tan(α + 90 ) cot(α 180 ) = cot(α) cot(α) = 2 cot(α) = cos(α)

2 cos(α) cos(α)

cos(α)

2 cos( α)

sin( α)

=

sin(α)

2

4

2 sin 2 (x) 3 cos 2 (x)+ 1 + tan 2 (x) = 2 sin 2 (x) 3 cos 2 (x)+

4

1+

sin 2 ( x ) cos 2 ( x )

=

= 2 sin 2 (x) 3 cos 2 (x)+

4

cos 2 (x)

sin 2 (x) = 2 sin 2 (x) 3 cos 2 (x)+ 4 cos 2 (x)

1

cos 2 (x) +

=

= 2 sin 2 (x) + cos 2 (x) = sin 2 (x) + sin 2 (x) + cos 2 (x) = sin 2 (x)+1

3 1 3 2 ln(x) − 1 3 ln(y ) + ln(y 3 )+ 4
3
1
3
2 ln(x) − 1 3 ln(y ) + ln(y 3 )+ 4 ln(
ln(x + y ) ln(x − y )
2 ln(x) − 1 3 ln(y ) + 3 ln(y ) − 4 ln(x)
x )
=
=
ln(x + y ) ln(x − y )
8
5 4 ln(x) +
ln(y y ) ) =
ln(x 5 4 · y 8 3 )
3
=
ln(x + y ) ln(x −
ln(x + y ) ln(x − y )
x
1
1 4
=
1
1
3
21
13 − 5x +11 +7
1
=
√ 2
1+ √ 3 x − 1 − 1
a b
=
x 2 − a 2 + x 2 − ax
c
x 2 + ax
1
1 4
1 4
=
| +
3 −
1
1
21
1
1
21
13 − 5x+11 +7
13 − 5x+11 +7 −
7
4
1
21 − 21
=
| Kehrwert
1
1
13 −
5x+11 +7

1

= 21 = 7

3

=

=

5 x + 11

x =

=

7

1

5x +11

1

13

1

13

5x +11 +7

1

13

2

5

| − 7+

|

| − 11

|

1

5x +11

Kehrwert

: 5

1

( 1+

3 ) x1 1

1

( 1+ 3 )

x1

1+ 3 x 1

=

=

=

2

1+ 2

1

1+ 2

| +1

| Kehrwert

| ln anwenden

1 ⇔ (x − 1) ln 1+ √ 3 = ln | : ln 1+
1
(x − 1) ln 1+ √ 3
=
ln
| : ln 1+ √ 3 | +1
1+ √ 2
ln ( 1+
√ 2 )
x
=
1 −
ln ( 1+
3 )
a
b
c
=
x 2 − a 2 + x 2 − ax
x 2 + ax
a
b
c
=
| Nenner f aktorisieren
| · x(x − a )(x + a )
( x − a )( x + a ) + x ( x − a )
x ( x
+ a )
x ( x − a )( x + a ) =0
ax + b (x + a )
=
c (x − a )
⇔ (a + b )x + ba
=
cx − ca
⇔ (a + b − c )x
= − ba − ca
| als P olynom von x schreiben
| − cx − ba
| : (a + b − c )
a + b− c =0
ab− ac
= a ( b+ c )
x
=
a + b− c
c − a − b
x
0 , a, − a
c = a + b
a
= 0 b + c
= 0
a = 0
b + c = 0
11
2 1
6
= 3 + ln(x 2 + e )
√ 3 x +3+1
√ 5 x − 6
=1
1 1
5 − 2 x >
1 − √ 2

e

R

11

6

7

6

6

7

=

3 +

2

1

ln( x 2 + e)
1

e 6 7

=

ln( x

2 + e)

= ln(x 2 + e )

=

x 2 + e

6 2

e 7 e =

x

| 4

6

|

Kehrwert

|

Exponentieren

| − e

3 x + 3

0 x ≥ − 1

5 x 6

0

x

6

5

x >

6

5

( 6

5

; )

√ 3x +3+1 √ 5x − 6
3x +3+1
5x − 6

3 x +3+1

3 x +3+1 2

3x +3+1+2 √ 3x +3
3x +3+1+2 √ 3x +3

2 3 x + 3

3 x + 3

3 x + 3

22

⇔ − 22

169 88

4

4

= 81

4

= ( 9 ) 2 ±

2

9

2

13